The mediating role of green innovation in the relationship between critical success factors and sustainability performance of energy firms in Indonesia - DwiKristina, Anggita; Jaharuddin, Nor Siah; Mansor, Zuraina (Auricle Global Society of Education and Research, 2024)
This research aims to investigate the relationship between critical internal and external success factors with Green Innovation and Sustainability Firm Performance of energy companies in Indonesia. The research method used is SEM-PLS path analysis using data from 96 energy companies in Indonesia. The results show that Internal Success Factors have a significant influence on Green Innovation and Sustainability Firm Performance. Likewise, external factors also have a significant influence on Green Innovation and Sustainability Firm Performance. Apart from that, Green Innovation has a significant influence on Sustainability Firm Performance. Path analysis also shows that Internal Success Factors and External Factors have an influence not only directly, but also through the mediator Green Innovation on Sustainable Firm Performance. These results underline the importance of internal and external success factors in driving Green Innovation and Sustainability Firm Performance in the context of the energy industry in Indonesia. The practical implication of this research is that energy companies need to pay attention to sustainability factors in their business strategies to achieve better sustainability performance.